Bismaleimide cross‐linked anthrax toxin forms functional octamers with high specificity in tumor targeting. (17th April 2019) - Fischer, Elyse S.; Campbell, Warren A.; Liu, Shihui; Ghirlando, Rodolfo; Fattah, Rasem J.; Bugge, Thomas H.; Leppla, Stephen H.
Abstract: In recent years, anthrax toxin has been reengineered to act as a highly specific antiangiogenic cancer therapeutic, shown to kill tumors in animal models. This has been achieved by modifying protective antigen (PA) so that its activation and toxicity require the presence of two proteases, matrix metalloproteinase (MMP) and urokinase plasminogen activator (uPA), which are upregulated in tumor microenvironments. These therapeutics consist of intercomplementing PA variants, which are individually nontoxic, but form functional toxins upon complementary oligomerization. Here, we have created a dual‐protease requiring PA targeting system which utilizes bismaleimide cross‐linked PA (CLPA) rather than the intercomplementing PA variants. Three different CLPA agents were tested and, as expected, found to exclusively form octamers. Two of the CLPA agents have in vitro toxicities equal to those of previous intercomplementing agents, while the third CLPA agent had compromised in vitro cleavage and was significantly less cytotoxic. We hypothesize this difference was due to steric hindrance caused by cross‐linking two PA monomers in close proximity to the PA cleavage site. Overall, this work advances the development and use of the PA and LF tumor‐targeting system as a practical cancer therapeutic, as it provides a way to reduce the drug components of the anthrax toxin drug delivery system from three to two, which may lower the cost and simplify testing in clinical trials. HIGHLIGHT: Previously, anthrax toxin has been reengineered to act as a highly specific antiangiogenic cancer therapeutic. Here, we present a version, which utilizes bismaleimide cross‐linked protective antigen (PA) rather than intercomplementing PA variants. This advances the development of anthrax toxin as a practical cancer therapeutic as it reduces the components of the drug delivery system to two, which may lower the cost and simplify testing in clinical trials.